The effectiveness of affordable housing scheme in Malaysia / Fara Raudah Mohd Razali and Ashrof Zainudin - Mohd Razali, Fara Raudah; Zainudin, Ashrof (2023)
This research aims to study the effectiveness of affordable housing scheme in Malaysia that was introduced by the government as there are issues arise. The objectives are 1. To investigate the issues that arise from the affordable housing scheme; 2. To identify the element for improvement of affordable housing scheme in future; 3. To propose initiatives and recommendation to reduce issues that regularly arise. The issues arise has raised questions about the effectiveness of the affordable housing scheme. 100 respondents were given a questionnaire as part of the primary data collection and the questionnaire were distributed in Johor Bahru because it is one of the busiest town and high cost of living. Findings of this study were concluded that the affordable housing scheme is not yet succeeded their main objective because most of the respondents were feeling unsatisfied with the price which means the affordable home are not affordable yet for them. Further research should be made for each state in Malaysia and a comparison of each state can be made.